2005
DOI: 10.1111/j.1365-2249.2005.02826.x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and functional evaluation of a single-chain antibody against HIV-1 external glycoprotein gp120

Abstract: SummaryThe HIV-1 envelope glycoprotein surface subunit gp120 is an attractive target for molecular intervention. This is because anti-HIV-1 gp120 neutralizing antibodies display the potential ability to inhibit HIV-1 infection. The present investigation describes the construction of a genetically engineered single chain antibody (scFv102) against HIV-1 gp120, its expression and functional evaluation. The parental hybridoma cell line (102) produces an immunoglobulin directed against the conserved CD4-binding re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Antibodies represent a special case [106] for which the relationship between the sequence and structure of the functional site is well defined. This has allowed the rational design of new antibodies with different biochemical properties, which have had broad application in therapy and research [107][108][109][110][111]. More complex is the prediction of enzyme structures to be subsequently used in the design of enzyme inhibitors.…”
Section: Model Accuracy and Applicationsmentioning
confidence: 99%
“…Antibodies represent a special case [106] for which the relationship between the sequence and structure of the functional site is well defined. This has allowed the rational design of new antibodies with different biochemical properties, which have had broad application in therapy and research [107][108][109][110][111]. More complex is the prediction of enzyme structures to be subsequently used in the design of enzyme inhibitors.…”
Section: Model Accuracy and Applicationsmentioning
confidence: 99%
“…Thus far, several neutralizing scFv antibodies have been produced against a number of viruses including scFv antibodies against human immunodeficiency virus type 1 (HIV-1) [18], scFvs to human cytomegalovirus [19] and scFv against influenza A virus H5N1 subtype [20] that can inhibit viral infections in vitro. Nejatollahi et al described a neutralizing scFv-phage antibody against glycoprotein D of HSV-1 with neutralizing effect of 76%, which was capable of neutralizing HSV-1 and inhibiting virus entry to host cell [21].…”
Section: Introductionmentioning
confidence: 99%
“… 15 Numerous scFvs and dAb variants and camel-derived antibodies have now been identified that retain the broadly neutralizing anti-HIV activity. 16–22 Among these broadly neutralizing antibody fragments are ScFv-m9, 23 , 24 dAb-m36, 25 , 26 and dAb-36.4 variant 19 that bind CD4i regions and facilitate neutralization of a broad range of HIV isolates.…”
Section: Introductionmentioning
confidence: 99%